2022
DOI: 10.3390/cells11020229
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular HSP90α Induces MyD88-IRAK Complex-Associated IKKα/β−NF-κB/IRF3 and JAK2/TYK2−STAT-3 Signaling in Macrophages for Tumor-Promoting M2-Polarization

Abstract: M2-polarization and the tumoricidal to tumor-promoting transition are commonly observed with tumor-infiltrating macrophages after interplay with cancer cells or/and other stroma cells. Our previous study indicated that macrophage M2-polarization can be induced by extracellular HSP90α (eHSP90α) secreted from endothelial-to-mesenchymal transition-derived cancer-associated fibroblasts. To extend the finding, we herein validated that eHSP90α-induced M2-polarized macrophages exhibited a tumor-promoting activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…It is known that HSP90α interacts also with LRP1. 21 38 Zou et al 19 found that two evolutionarily conserved lysine residues, Lys-270 and Lys-277, of HSP90α contained in the subfragments F-5 and F-6 were responsible for the binding of HSP90α to LRP1 on human cancer cells. In contrast, we demonstrated that these subfragments failed to upregulate PD-L1 on human monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that HSP90α interacts also with LRP1. 21 38 Zou et al 19 found that two evolutionarily conserved lysine residues, Lys-270 and Lys-277, of HSP90α contained in the subfragments F-5 and F-6 were responsible for the binding of HSP90α to LRP1 on human cancer cells. In contrast, we demonstrated that these subfragments failed to upregulate PD-L1 on human monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently published that rHSP90α can trigger both LRP1 and TLR4 on THP1-derived macrophages, RAW264.7 macrophage cell line and bone marrow-derived macrophages, resulting in the upregulation of CD163, CD204, IL-10 and downregulation of TNF-α, IL-1β as well as in the depletion of CD4 T cells from the pancreatic tumor. 21 It is possible that rHSP90α in myeloid cells forms a complex with TLR4 and LRP1, in which TLR4 plays a pivotal role. Moreover, HSP90α and HSP90β were reported to be expressed on the surface of monocytes and macrophages and to participate in cytokine response to TLR4 ligands by building a signaling complex with TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with Hsp90 inhibitor selectively interfered with the tumorigenic MIF that assisted in promoting angiogenic gene expression in tumor cells (Klemke et al, 2021). Extracellular Hsp90 also induced M2-polarized macrophages to demonstrate tumorpromoting activities including upregulation of M2 markers, phagocytosis repressors, and angiogenesis activators mediated through several signaling pathways (Fan et al, 2022). Extracellular Hsp90 is also involved in lymphangiogenesis.…”
Section: Angiogenesismentioning
confidence: 99%
“…Additionally, VEGF-C treatment is known to stimulate OC in a similar manner as M-CSF [ 107 ]. Macrophages (OC progenitors) and MSC are also known to secrete various VEGF factors, including VEGF-C [ 8 , 108 ]. These VEGF-C sources might readily further stimulate lymphatic invasion and trigger bone resorption.…”
Section: Proposed Cla Osteopathymentioning
confidence: 99%